The Impact of Reading Habits and Their Antecedents on The Subjective WellBeing of Malaysian Youths - Kaur, H.; Rasiah, R.; A.H., Baharom; Habibullah, M.S.; Turner, J.J.; Dayang Affizzah, Awang Marikan (Ani Publishing Ltd., 2022)
Purpose The well-being of youths is a crucial concern, and the pandemic has further expatiated their well-being There is a need to foster positive well-being among youths experiencing a rapid developmental change in their lives and choosing their environments which can be accomplished through reading. The goal of this study was to determine the perceived influence of reading attitude, perceived behavioural control, and subjective norm on adolescents' reading habits and the relationship between reading habits and subjective well-being among youths aged 15 to 24 in East and West Malaysia. Methodology The current study used a survey questionnaire gathered from 813 responders from East and West Malaysia and the analysis utilized AMOS-Structural Equation Modeling. Findings The data reveal that reading attitude and subjective norms positively and significantly influence reading habits, although perceived behavioural control has a detrimental effect. In addition, the findings support the mediation of reading habits in the relationship between reading attitude and subjective well-being and between perceived behavioural control and subjective well-being. Implications to Research and Practice This study would provide educators and policymakers with insight into the most effective strategies for instilling good reading habits in youths by transforming the curriculum and what happens inside the classroom to provide much-needed valuable classroom time to engage youth in reading